(untitled) (Nordic Journal of African Studies, 1992)
Finnish and Tanzanian folklore are here compared from the viewpoint of their various forms and functions. In order to facilitate the analysis, a brief historical survey is made of the folkloristic studies in these societies. In Finland the study of folklore had a vital role in the emergence of the Finnish national consciousness in the 19th century. A condensed symbol of this new identity was the Kalevala, an epic poem compiled and adapted from older oral material by Elias Lönnrot. Themes and symbols from this old folklore have been extensively used in music, art, theatre, cinema, trade marks etc. In Tanzania the study of folklore has been casual so far. Some systematic surveying has been initiated in the Islands and the coastal areas, but the folklore of the continent is still largely unknown. Small samples of folklore have been published as booklets and used in school teaching. It is suggested that a plan be made for the comprehensive survey, collection and study of Tanzanian folklore. It is further suggested that although Finland and Tanzania are ethnically and linguistically quite different, they still have much in common in their struggle for national identity and cultural freedom, a struggle in which indigenous cultures and languages have a vital role to play.